2022
DOI: 10.1097/mcp.0000000000000929
|View full text |Cite
|
Sign up to set email alerts
|

Advances in bronchoscopic optical coherence tomography and confocal laser endomicroscopy in pulmonary diseases

Abstract: Purpose of reviewImaging techniques play a crucial role in the diagnostic work-up of pulmonary diseases but generally lack detailed information on a microscopic level. Optical coherence tomography (OCT) and confocal laser endomicroscopy (CLE) are imaging techniques which provide microscopic images in vivo during bronchoscopy. The purpose of this review is to describe recent advancements in the use of bronchoscopic OCT- and CLE-imaging in pulmonary medicine.Recent findingsIn recent years, OCT- and CLE-imaging h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Needle‐based confocal laser endomicroscopy (nCLE) is a laser‐based imaging technique that utilizes fluorescence for real‐time microscopic imaging at the biopsy needle tip 7,8 . Recent studies demonstrated that nCLE‐imaging in mediastinal lymph nodes and lung nodules can detect malignancy based on three nCLE criteria (enlarged pleomorphic cells, dark clumps and directional streaming) 9–12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Needle‐based confocal laser endomicroscopy (nCLE) is a laser‐based imaging technique that utilizes fluorescence for real‐time microscopic imaging at the biopsy needle tip 7,8 . Recent studies demonstrated that nCLE‐imaging in mediastinal lymph nodes and lung nodules can detect malignancy based on three nCLE criteria (enlarged pleomorphic cells, dark clumps and directional streaming) 9–12 .…”
Section: Introductionmentioning
confidence: 99%
“…Needle-based confocal laser endomicroscopy (nCLE) is a laser-based imaging technique that utilizes fluorescence for real-time microscopic imaging at the biopsy needle tip. 7,8 Recent studies demonstrated that nCLE-imaging in mediastinal lymph nodes and lung nodules can detect malignancy based on three nCLE criteria (enlarged pleomorphic cells, dark clumps and directional streaming). [9][10][11][12] Currently, (robotic-)bronchoscopic nCLE-imaging of peripheral lung nodules is used in research and selected clinical settings for real-time fine-tuning of the needle positioning.…”
Section: Introductionmentioning
confidence: 99%